Incidence of herpes zoster and post-herpetic neuralgia in Italy: Results from a 3-years population-based study - Cristiano Alicino; Cecilia Trucchi; Chiara Paganino; Ilaria Barberis; Sara Boccalini; Domenico Martinelli; Barbara Pellizzari; Angela Bechini; Andrea Orsi; Paolo Bonanni; Rosa Prato; Stefania Iannazzo; et al. (Taylor & Francis Group, 2017)
Herpes Zoster (HZ) and its main complication, post-herpetic neuralgia (PHN), represent important public health issues because of their relevant burden among older adults. However, data on the epidemiology of HZ and PHN in Italy are very limited. A population-based study was performed by seeking for cases of HZ and PHN, occurred in the period 2013-2015, in the clinical charts of 56 General Practitioners working in 4 Italian Regions (Liguria, Puglia, Toscana and Veneto). The main objective of the study was to estimate the incidence of HZ and the proportion of PHN (at 1 and 3 mo from the onset of HZ; PHN1 and PHN3) among people aged ≥ 50 y. Overall, 598 cases of HZ were identified over 93,146 person-years of observation, thus corresponding to an overall incidence of 6.42 (IC95%: 5.93 - 6.95) HZ cases per 1,000 person-years. The incidence of HZ increased with age and was higher in female than in male. In total, 22.7%, 12.7%, and 2.4% of HZ cases suffered PHN at 1 and 3 mo and 1 y from the onset of acute episode. The proportions of these complications significantly increased with age, with the peak occurring in people aged ≥ 85 y. Four per cent of patients suffered ophthalmic zoster. The study provided an update of the epidemiological burden of HZ and PHN in Italy, confirming the relevant burden of the disease in the elderly population. The study was funded by the Italian Ministry of Health, Center for Disease Prevention and Control (CCM) in 2013.